I'm not really here - Allen, Tim, 1953- (New York : Hyperion, 1996)
"I'm Not Really Here deals, in the Tollman's inimitable way, with some of the urgent questions a man faces at midlife, from "What is real?" to what should he eat for breakfast ("The gummy cinnamon buns or the cereal no one can pronounce? Moose Life, Mouse licks"). This book is culmination of a five-year journey of self-discovery. It will surprise and challenge, make you wonder and think, and induce laughter on every page.
Includes bibliographical references (p. 255).
Keywords: Men -- Humor; Midlife crisis -- Humor